COMPARISON OF ORAL VERSUS VAGINAL PROGESTERONE IN THE PREVENTION OF PRETERM LABOR AND ITS CORRELATION WITH CERVICAL LENGTH ON TRANSVAGINAL SONOGRAPHY (The Research of Medical Science Review, 2025)
Background: The prevention of preterm labor remains a major challenge in obstetrics due to its strong association with neonatal morbidity and mortality. Progesterone therapy is widely used in women at high risk, but the optimal route of administration—oral or vaginal—remains unclear. Objectives: To compare the efficacy of oral versus vaginal progesterone in preventing preterm labor and to evaluate their correlation with cervical length measured via transvaginal sonography. Study Design & Setting: This was a prospective, comparative observational study conducted at the Department of Obstetrics and Gynecology DHQ Teaching Hospital Mirpur AJK. Methodology: A total of 150 pregnant women at 16–24 weeks of gestation with cervical length <25 mm on transvaginal ultrasound were enrolled and randomly allocated into two equal groups. Group A received oral progesterone (Dydrogesterone 10 mg twice daily) while Group B received vaginal progesterone suppositories (Micronized Progesterone 200 mg once daily). Cervical length was measured every two weeks. The primary outcome was the incidence of preterm labor before 37 weeks. Secondary outcomes included changes in cervical length and treatment tolerability. Results: Preterm labor occurred in 28.0% of women in the oral group and 14.7% in the vaginal group (p = 0.046). Vaginal progesterone showed significantly better preservation of cervical length at 4 and 6 weeks. Compliance was good in both groups, with mild adverse effects varying by route. Conclusion: Vaginal progesterone is more effective than oral progesterone in preventing preterm labor and maintaining cervical length in high-risk pregnancies.